Concurrent extrapulmonary bronchopulmonary sequestration and bronchogenic cyst - Lindel Dewberry, MD; Jason Bunn, BS; Csaba Galambos, MD, PhD; Henry L. Galan, MD; Michael V. Zaretsky, MD; Nicholas Behrendt, MD; Regina Reynolds, MD; Mariana Meyers, MD; Ahmed I. Marwan, MD; Kenneth W. Liechty, MD (Elsevier, 2018)
A prenatal ultrasound (US) at 21 weeks estimated gestational age (EGA) identified a left intrathoracic homogenously echogenic microcystic mass with mediastinal shift and a CPAM volume ratio (CVR) of 0.78 (Fig. 1). A fetal magnetic resonance imaging (MRI) study confirmed the US findings. MRI and US were repeated at 35 weeks EGA demonstrating a CVR of 0.36 and a spontaneous decrease in size of the previously identified mass. Moreover, an intralesional, fluid filled dilated bronchus was identified that connected to the esophagus and showed mild branching. This finding was thought to represent an esophageal bronchus. Prenatal echocardiogram demonstrated normal cardiac anatomy and function. The patient was delivered vaginally at 38 weeks EGA with no respiratory distress after delivery. The patient was discharged at this time with planned outpatient follow-up. Outpatient contrast CT at three months of age demonstrated a left BPS supplied by the celiac axis and a fluid filled branching structure within the sequestration suspicious for esophageal bronchus. At four months of age, the patient underwent a left, muscle sparing thoracotomy, where the bronchopulmonary sequestration was excised and an adjacent cyst was enucleated. Pathology demonstrated extralobar bronchopulmonary sequestration with a separate foregut malformation most consistent with bronchogenic cyst.